2016
DOI: 10.5051/jpis.2016.46.4.277
|View full text |Cite
|
Sign up to set email alerts
|

The association between radiographic embrasure morphology and interdental papilla reconstruction using injectable hyaluronic acid gel

Abstract: PurposeThe purpose of this study was to evaluate the clinical efficacy of enhancing deficient interdental papilla with hyaluronic acid gel injection by assessing the radiographic anatomical factors affecting the reconstruction of the interdental papilla.MethodsFifty-seven treated sites from 13 patients (6 males and 7 females) were included. Patients had papillary deficiency in the upper anterior area. Prior to treatment, photographic and periapical radiographic standardization devices were designed for each pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
3
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(53 citation statements)
references
References 15 publications
0
45
3
5
Order By: Relevance
“…Up to 3 applications were made in 3-week intervals between them in 14 sites: obtaining 100% filling in 2 sites; 94-97% growth in 7 sites; 76-88% growth in 3 sites; and 1 site that had a 57% growth. These results contrast to 2 recent studies from Lee et al 38,39 using photographic methodology of more effective measurements, using up to 5 applications of commercial hyaluronic acid gel in 3-week intervals in 43 sites where 67% of the black spaces of the sites were 100% filled. The remaining sites had an average filling of 87%.…”
Section: Discussioncontrasting
confidence: 72%
“…Up to 3 applications were made in 3-week intervals between them in 14 sites: obtaining 100% filling in 2 sites; 94-97% growth in 7 sites; 76-88% growth in 3 sites; and 1 site that had a 57% growth. These results contrast to 2 recent studies from Lee et al 38,39 using photographic methodology of more effective measurements, using up to 5 applications of commercial hyaluronic acid gel in 3-week intervals in 43 sites where 67% of the black spaces of the sites were 100% filled. The remaining sites had an average filling of 87%.…”
Section: Discussioncontrasting
confidence: 72%
“…55,57,62 More studies are needed to confirm the possible use of filler materials to increase papilla height and volume in less demanding situations because there are conflicting results of its real potential. 59,61 Greater defects may be treated by using gingivashade ceramics, but this rehabilitation is not free of esthetic risk because different factors may influence the outcomes, especially in patients with a high smile line and defects restricted to one anterior tooth, which shows the transition between the restoration and the mucosa. 84…”
Section: Discussionmentioning
confidence: 99%
“…Papilla loss was also treated by using nonsurgical methods, such as repeated curettage, injections with micron ized acellular dermal g rafts or hyaluronic acid, and restorative or orthodontic procedures. 54,55,56,57,58,59 Several factors influence the treatment of papilla loss with filler materials, such as hyaluronic acid, and the clinical results obtained from human studies presented more promising results in areas between teeth 59,60 than implants. 61 Restorative or orthodontic procedures may be performed to condition the soft tissue and create interproximal papilla around implants.…”
Section: Papilla Lossmentioning
confidence: 99%
“…The technique was first described by Becker et al ( 10 ) in a pilot study treating 14 sites in 11 patients. Several other reports followed that work ( 11 - 14 ). Those studies reported variable outcomes with differing success rates, which are difficult to compare due to the lack of appropriate control sites and the different number of treatment sessions per individual.…”
Section: Introductionmentioning
confidence: 87%